Magnetoliposomes based on manganese ferrite/gold nanoparticles for applications in cancer therapy - Rodrigues, Ana Rita Oliveira (2018)
In this work, different types of magnetic/plasmonic MnFe2O4/Au nanoparticles were prepared, including core-shell and decorated nanoparticles. The structural, spectroscopic and magnetic properties were evaluated. The nanoparticles were covered with a lipid bilayer or entrapped in liposomes.